Erratum: miR-15a/miR-16 down-regulates BMI1, impacting Ub-H2A mediated DNA repair and breast cancer cell sensitivity to doxorubicin. Issue 1 (December 2017) - Patel, Nibedita; Garikapati, Koteswara; Pandita, Raj; Singh, Dharmendra; Pandita, Tej; Bhadra, Utpal; Bhadra, Manika
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.